2015
DOI: 10.1111/j.1755-3768.2015.0586
|View full text |Cite
|
Sign up to set email alerts
|

Changes in choroidal thickness after intraocular pressure reduction following trabeculectomy

Abstract: PurposeTo evaluate changes of choroidal thickness (CT) after an acute reduction in intraocular pressure (IOP) following trabeculectomy.MethodsSubfoveal and peripapillary CT and IOP were measured in 40 glaucomatous eyes (40 patients) 1 day before, 1 week and 1 month after the trabeculectomy. The choroid was evaluated using spectral domain optical coherence tomography enhanced depth imaging at the fovea and 1.7 mm superior, temporal, inferior and nasal to a optic nerve head centre. Biometry was performed preoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…Although we measured LC depth from the level of the BMO, we also measured choroidal thickness before and after surgery to overcome the limitation of this method. Consistent with previous observations, [30][31][32] we found that the choroid was thicker after than before surgery. Thickening of the choroid increases the distance between the BMO and the anterior LC surface, resulting in an overestimation of LC depth.…”
Section: Discussionsupporting
confidence: 93%
“…Although we measured LC depth from the level of the BMO, we also measured choroidal thickness before and after surgery to overcome the limitation of this method. Consistent with previous observations, [30][31][32] we found that the choroid was thicker after than before surgery. Thickening of the choroid increases the distance between the BMO and the anterior LC surface, resulting in an overestimation of LC depth.…”
Section: Discussionsupporting
confidence: 93%
“…Significant changes in LC position [1][2][3][4] and CT have been reported [17][18][19][20][21][22] after filtering surgery. CT can influence the LCD assessment as measured from BMO reference line, [6][7][8][9] and it is a dynamic parameter depending on several factors including IOP fluctuations.…”
Section: Discussionmentioning
confidence: 97%
“…For detecting CT changes, we estimated a sample size of 36 eyes to reach an error alpha = 0.05 and a statistical power of 80%. 19 One-sample Kolmogorov-Smirnov test was used to verify normal distribution. The quantitative information was expressed as mean and standard deviation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,12 Interestingly, clinical evidence suggests that IOP and choroidal volume themselves may be linked. 45,46 A reduction of IOP via trabeculectomy or deep sclerectomy has been shown to cause a subsequent change in choroidal thickness. Thus, studies aimed at understanding the interaction of IOP and choroid volume and their combined influence on ONH biomechanics will be critical in the future.…”
Section: Discussionmentioning
confidence: 99%